Generation X and Purchase Intention Toward Green Cosmetic and Skin Care Products - Nor Fairuz Syazana Nor Fauzi,; Raemah Abdullah Hashim, (Open University Malaysia (OUM), 2015)
The significant increase of green awareness among people throughout the world has created tremendous implications on the cosmetics industry. However, in Malaysia, the market for green cosmetics and skin care is still in its infancy. Consequently, this study had been undertaken to investigate generation X‘s behavior in purchasing green products which is crucial since they form one of the biggest target groups among cosmetic users. Thus, this study examines Malaysia’s Generation X consumers’ purchasing intention for green cosmetics and skin care products. Specifically, the current study examines the relationship of psychological factors of consumer values i.e. health consciousness, environmental consciousness, self-image consciousness among generation X’s attitude towards purchase intention of green cosmetics and green skin care in Malaysia. The results of the regression analyses showed that health consciousness has significant relationship with attitude towards the purchasing of green cosmetics and skin care products. However, the reverse was found on environmental consciousness and self image that indicated no relationship to purchase intension. Consequently, attitude factor was found to mediate the relationship between consumer values and green purchase intention. In addition, the findings from the analyses also revealed that past purchase experience was the most significant determinant to purchase intention. This study implies that producers of green products must be able to convey their green message to the intended target market, especially when these groups are actively engaged in environmental practices and issues. Future researches should consider a nationwide survey covering samples from other generation groups as well as be gender based which would be more significant in making a generalization [ABSTRACT BY AUTHORS]